2019
DOI: 10.1371/journal.pone.0216542
|View full text |Cite
|
Sign up to set email alerts
|

Public attitudes towards genetically modified polled cattle

Abstract: Genetic modification of farm animals has not been well accepted by the public. Some modifications have the potential to improve animal welfare. One such example is the use of gene editing (i.e. CRISPR (clustered regularly interspaced short palindromic repeats)) to spread the naturally occurring POLLED gene, as these genetically hornless animals would not need to experience the painful procedures used to remove the horns or horn buds. The aim of the current study was to assess public atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 35 publications
6
46
1
2
Order By: Relevance
“…However, it has been shown that simply informing lay citizens of the technical reasons behind practices that they may perceive as detrimental to animal welfare does not necessarily lead to support [ 55 , 57 , 59 , 61 ]. Yet, reducing animal suffering may be a powerful argument for the public to accept technologies that they otherwise reject on the grounds of risk for humans [ 33 , 56 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that simply informing lay citizens of the technical reasons behind practices that they may perceive as detrimental to animal welfare does not necessarily lead to support [ 55 , 57 , 59 , 61 ]. Yet, reducing animal suffering may be a powerful argument for the public to accept technologies that they otherwise reject on the grounds of risk for humans [ 33 , 56 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…To maintain public trust, it is essential that these technologies are satisfactorily proven safe and effectively reduce animal suffering, as these are important conditions for acceptance [ 33 , 62 , 63 ]. In the case of immunocastration, there is sufficient scientific knowledge demonstrating the absence of residues potentially harmful to humans (see [ 18 , 20 ]).…”
Section: Discussionmentioning
confidence: 99%
“…For many, issues related to technology do not elicit a yes or no response but a case-by-case deliberation. Reports of surveys of public opinion are starting to emerge [52][53][54] . These show general support for application of the technology, with a parallel cry for more information so that informed opinions can be developed [55] .…”
Section: Summary and Future Perspectivementioning
confidence: 99%
“…17,18 A 2019 study of public perceptions of genetically modifying dairy cattle so that they would be born without horns found that approximately half of respondents held a negative attitude toward the modification for ''moral considerations.'' 19 The authors reporting the survey results exemplified the category of moral considerations with the quote, ''I think that it is 'playing God' and is immoral and unethical.'' 19 The British watchdog organization, Human Genetics Alert, describes human germline editing as ''playing God'' and compares it to climate change in its potential for creating disaster.…”
Section: Introductionmentioning
confidence: 99%
“…19 The authors reporting the survey results exemplified the category of moral considerations with the quote, ''I think that it is 'playing God' and is immoral and unethical.'' 19 The British watchdog organization, Human Genetics Alert, describes human germline editing as ''playing God'' and compares it to climate change in its potential for creating disaster. 20 More direct objections to using CRISPR for human germline modification as ''playing God'' are also well established in the public discourse.…”
Section: Introductionmentioning
confidence: 99%